1998
DOI: 10.1016/s1097-2765(00)80059-3
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Action Imitates Huntington's Disease: Selective Polymerization of Huntingtin Containing Expanded Polyglutamine

Abstract: Different proteins bearing polyglutamine of excessive length are lethal to neurons and cause human disease of the central nervous system. In parts of the brain affected by Huntington's disease, the amount of the huntingtin with expanded polyglutamine is reduced and there appear huntingtin-containing polymers of larger molecular weight. We show here that huntingtin is a substrate of transglutaminase in vitro and that the rate constant of the reaction increases with length of the polyglutamine over a range of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
148
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(148 citation statements)
references
References 34 publications
0
148
0
Order By: Relevance
“…Increasing the length of synthetic polyQ increased the reactivity per Q residue in transglutaminase-catalyzed coupling to spermine (11). Our experiments on full-length huntingtin containing glutamine repeats of different length showed that, as in the peptides, the activity of huntingtin as a substrate for transglutaminase increased sharply with length of the polyQ (12).…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…Increasing the length of synthetic polyQ increased the reactivity per Q residue in transglutaminase-catalyzed coupling to spermine (11). Our experiments on full-length huntingtin containing glutamine repeats of different length showed that, as in the peptides, the activity of huntingtin as a substrate for transglutaminase increased sharply with length of the polyQ (12).…”
mentioning
confidence: 68%
“…It has been reported (12,31,48) that in the cortex of patients with Huntington's disease, expanded huntingtin is replaced by a broad band or smear containing huntingtin and extending upward from the expected position of expanded huntingtin. We prepared extracts of cortex and cerebellum from four patients with juvenile Huntington's disease, obtained from the Harvard Brain Tissue Resource Center.…”
Section: Soluble Oligomer Containing Expanded Huntingtin In the Cerebralmentioning
confidence: 99%
“…It has been suggested that this enzyme is involved in NII formation in HD (Kahlem et al, 1998). However, the number of striatal and cortical aggregates are increased in a transgenic mouse model generated by crossbreeding R6/1 mice with "tissue" Tgase knock-out mice [R6/1, TG2 (−/−) mice], suggesting that this may not be the case (Mastroberardino et al, 2002).…”
Section: Transglutaminase Inhibitionmentioning
confidence: 99%
“…8 Several reports suggest that in vitro aggregation may occur both through polar zippers formation and/or protein cross-linking catalysed by TG2. 9,10 Recent studies showed that TG2 does not interact with mutant huntingtin in cellular models and it is not involved in the assembly of NIIs, 11 but despite these in vitro indications, no in vivo evidence for either models was so far obtained.…”
Section: Introductionmentioning
confidence: 99%